2015
DOI: 10.1111/mbe.12086
|View full text |Cite
|
Sign up to set email alerts
|

Educational Neuromyths Among Teachers in Latin America

Abstract: Neuroscientific knowledge has undeniably gained interest among educators worldwide. However, not all "brain facts" believed by teachers are supported by science. This study sought to evaluate the belief in these so-called neuromyths among 3,451 Latin American teachers. We found that, consistent with prior research among teachers in other geographic areas, teachers in Latin America hold major misconceptions about neuroscience, especially as it relates to factual information about its structure and functioning. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
82
4
31

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 103 publications
(148 citation statements)
references
References 20 publications
13
82
4
31
Order By: Relevance
“…In many cases, these neuromyths are the outcomes of translation mistakes or sufficient translation attempts (Daniel, 2012). Therefore, the need for acceptable translation and for the original article not losing its meaning, has come to the forefront (Gleichgerrcht et al, 2015). When it is considered that the deceptive use of science will have a cost in education, it is concluded that it is essential not to ignore the researches carried out on the subject.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In many cases, these neuromyths are the outcomes of translation mistakes or sufficient translation attempts (Daniel, 2012). Therefore, the need for acceptable translation and for the original article not losing its meaning, has come to the forefront (Gleichgerrcht et al, 2015). When it is considered that the deceptive use of science will have a cost in education, it is concluded that it is essential not to ignore the researches carried out on the subject.…”
Section: Discussionmentioning
confidence: 99%
“…In a way, this might lead to an unfavorable outcome, because this enthusiasm in ne information might cause the teachers to be inclined to encounter fake science at the same time. At this point, it is the relevant stakeholders' duty to provide reliable information for the teachers and to make correct translation (Pasquinelli, 2012;Gleichgerrcht et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Essa desinformação acaba por ser propagada, mesmo dentro de salas de aula, por educadores a seus alunos. Além disso, Gleichgerrcht et al (2015) demonstram que educadores que acreditam ter maior conhecimento sobre o sistema nervoso (porém não buscam informações fidedignas) são mais suscetíveis a crenças nos "neuromitos" em comparação a outros profissionais sem esse suposto conhecimento prévio.…”
Section: Neurociências E Educaçãounclassified